Overview of How to Stop Damage Caused by Nuisance Wildlife in Your Yard - Holly K. Ober; Arlo Kane (EDIS)
In Florida, we are fortunate to have a wide variety of wildlife to watch and enjoy. Indeed, many homeowners attempt to attract particular types of wildlife to their yards to watch. However, wild animals can become a nuisance in some situations. This 4-page fact sheet is the first in a five-part series describing tactics you can use to cope with wildlife that have become a nuisance. Here we suggest a sequence of steps you can implement when wildlife is causing damage in your yard. These suggestions should help reduce wildlife damage in a practical, humane, and environmentally responsible manner. Written by Holly K. Ober and Arlo Kane, and published by the UF Department of Wildlife Ecology and Conservation, October 2012.